PENDAPATAN BERDASARKAN STATUS PENGUASAAN LAHAN USAHATANI TEMBAKAU DAN PEMASARANNYA - Manalu, Arta Santrina; Sumantri, Bambang; Priyono, Basuki Sigit (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2018)
This study aimed to know the income to the tobocco farming and marketing channels, distribution and to determine the marketing marjin in Doloksaribu village Pagaran districts North Tapanuli district. This study uses descriptive and do purposive method location. Determination of farmer respondents is done by Stratified Random Sampling technique as much as 50 farmers, while to know the marketing channels used snowball sampling method. Types of data collected included primary data and secondary data. This study uses data were analyzed the farm income of tobacco farmers, analyze marketing channels and marketing margins.The results showed the average income of cash tenant farmers in the Doloksaribu village of Pagaran District is Rp.23.994.011,58 per hectare in one growing season is greater than the share tenant farmers on average earnings of Rp.21.051.624,77per hectare per cropping season and owner operatorRp.17.708.316,37per hectare per cropping season. The main marketing channel in the study area is from tobacco farmers (producers) to the consumer (the tobacco company). Tobacco marketing margin in the village Doloksaribu is very low (0) in the absence of marketing institutions that play a role in these activities so that the channel marketing is also short